ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN MATERI TEOREMA PYTHAGORAS - Dadang Anugrah Pangestu; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research was conducted to describe the mistakes made by students in the Pythagorean theorem materials when solving mathematical problems. This study was conducted using a qualitative description method in an MTs school in West Bandung District, where there are as many as 20 students in Class VIII A. This study uses descriptive tests to collect data. The stage of drawing conclusions is completed through data analysis, data collection and data simplification. The result of calculating the student's answer is part of the data processing technology. Then get the result that students have wrong answers when reducing data. The common mistakes made by students include errors in arithmetic operations, errors in conceptual understanding, errors in students' rush to answer questions that do not match the completion of the steps, and errors in understanding the language of the question.